Enhancement of activity against influenza viruses by combinations of antiviral agents. - Hayden, F G (1980)
In an investigation of alternative therapeutic approaches for the treatment of influenza virus infections, the antiviral activities of rimantadine hydrochloride, amantadine hydrochloride, ribavirin, and combinations of these drugs were assessed in vitro. Madin-Darby canine kidney cell monolayers were inoculated with recent isolates of influenza viruses at low multiplicities of infection, and virus titers were determined after 24 h. The combination of rimantadine and ribavirin resulted in an enhanced antiviral effect (a decrease in virus titer of > 1.0 log10 plaque-forming unit per ml at 24 h relative to the maximal effect of a single drug) against A/USSR/90/77/H1N1, A/Texas/1/77/H3N2, A/New Jersey/76/HSW1N1, and A/PR/834/H0N1 viruses. The degree of inhibition depended on the virus strain used, the drug concentrations, and the virus inoculum. Amantadine and ribavirin showed enhanced activity. Ribavirin in combination with high (50 micrograms/ml), but not low (1.56 to 25 micrograms/ml), concentrations of rimantadine showed an enhanced antiviral effect against B/Hong Kong/72 virus. An assay of Madin-Darby canine kidney cell proliferation in the presence of drugs showed that the enhanced inhibitory effect of drug combinations was not due to increased cytotoxicity.